S07-4 The need for systematic reviews addressing the epidemiologic evidence linking endocrine disrupting xenobiotics with male reproductive disorders. (1st September 2016) - Bonde, Jens Peter; Andersen, S; Glazer, CH; Hansen, CR; Hougaard, KS; Høyer, B; Hærvig, KK; Pedersen, SEB; Rylander, L; Specht, IO; Toft, G; Bräuner, EV
Abstract : Background and objective: More than 20 years ago it was hypothesised that pre- and early postnatal environmental xenobiotics with the potential to disrupt endogenous hormone signalling might be on the causal path to cryptorchidism, hypospadias, low sperm count and testis cancer. Several narrative reviews and weight of the evidence reports past years conclude that evidence has been accumulating to support the hypothesis. In particular one of these reviews has been criticised for preconceived views and selective reporting which has elicited a heated debate. The question is whether data now are available which allow systematic and transparent reviews of the epidemiological evidence and how such reviews should be conducted. We set out to identify available epidemiological evidence addressing male reproductive disorders following pre- and perinatal exposure and suggest methods for meta-analysis. Methods: We performed a systematic search in PubMed and Embase to identify published data on the risk of hypospadias, cryptorchidism, low sperm counts and testis cancer following pre- and early infant exposure to xenobiotic environmental chemicals that in at least one intact organism have shown adverse effects due to endocrine disruption. We only included peer reviewed papers providing data on exposure to specific chemicals in utero or early infancy documented by measurements in biological specimens (maternal blood or urine, placenta tissue, cord blood, breast milk) and studies extrapolating fetal or early life exposure by measurements in adult life. Results: We identified 24 independent studies that through 36 papers reported 116 associations between measured levels of endocrine disruptors and male reproductive disorders. Most studies addressed persistent organochlorines such as DDE (18 associations), PCBs (12 associations), DDT and HCB (each 12 associations) while studies on rapidly metabolised compounds as phthalate ethers and Bisphenol were few. The studies included altogether 2446 cases and 324 men provided semen samples. The completeness of reporting assessed by 11 items were considered very high (≥80%) in 14 of the studies but only 5 studies were considered at low risk of bias and confounding. Conclusion: Although the epidemiological literature database is limited when using highly strict criteria for evaluation it seems sufficient for quantitative meta-analysis addressing on the hypothesis on environmental endocrine disrupting chemicals and male reproductive disorders. Systematic reviews addressing other other outcomes are warranted